Pembinaan Literasi Media pada Pelajar SMA Ananda Kota Batam dalam Pencegahan Disinformasi di Era New Normal - Ageng Cindoswari; Kundori Kundori; Nurma Dhona Handayani; Nenti Siti Patimah; Tedy Yansyah; Qori Framana; Gustama Putra Rusli; Alfian Juanda Putra Porang (LPPM Universitas Putera Batam, 2023)
Media literacy education as a form of effort to prevent the negative side of globalization which cannot be stopped is very important to do because it is not only because of the needs of today's information society, but also UNESCO's international mandate for all countries in the world. Media literacy education is highly recommended to be carried out in formal institutions/organizations or in the school environment. SMA Ananda is one of the educational institutions in the city of Batam that requires assistance regarding media literacy, especially for students. This training is carried out with the aim of providing (1). Knowledge of students in the city of Batam about the benefits and uses of the internet, (2). Knowledge of students in the city of Batam regarding media literacy (3). Skills for students regarding the spread of disinformation in the new normal era. This coaching will be carried out using lecture, discussion, and practice methods with a duration of 1 hour per session for 4 meetings involving 3 assistants alternately and on a scheduled basis. This coaching will be given to students at Ananda High School in Batam City, totaling around 20-30 people which will be held in the January-December 2021 range.